ANALISIS PELAKSANAAN TINDAK LANJUT HASIL PEMERIKSAAN BPK RI ATAS LAPORAN KEUANGAN PEMERINTAH PROVINSI ACEH TAHUN 2015-2019 - Athiya Imtina Putri; Mulia Saputra (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2021)
The purpose of this study to analyze follow-up recommendations. The follow-up of the inspection results is analyzed from the response of the Inspectorate regarding the completion of the inspection results. In more depth, this research wants to examine the steps of policy makers in completing the findings of the audit report. This research is a qualitative research with descriptive research type. Data consists of primary and secondary data. Primary data were collected with indepth interviews. On the other hard, secondary data were employed by document analysis. The results showed that there were still recommendations that had not been resolved due to obstacles faced by the Officials/ASN related to resolutions such as problems with third parties, settlement related to assets, and other technical obstacles, namely officials/ASN who have died/retired/whose address is unknown, miscommunication, negligence, lack of understanding and other technical obstacles.